A multivalent peptide as an activator of hypoxia inducible factor-1 alpha - Kwon, Hyuk Sung; Park, Jiae; Park, Yong Keun; Ahn, Dae-Ro (Pergamon Press Ltd., 2013)
Hypoxia inducible factor-1 alpha (HIF-1 alpha) is a transcription factor found in mammalian cells under hypoxia. While HIF-1 alpha in hypoxia translocates to the nucleus where it transcribes the target genes including vascular endothelial growth factor (VEGF) mRNA, HIF-1 alpha is degraded under normoxia, which involves its proline hydroxylation and subsequent binding to the von Hippel-Lindau protein-Elongin B-Elogin C (VBC) complex. Previously, peptide inhibitors against this interaction between hydroxylated HIF-1 alpha and VBC have been developed to stabilize the transcriptional activity of HIF-1 alpha by preventing the degradation of the protein even under normoxia. Despite the specific inhibition by these peptides, their poor inhibition potency needs to be improved for further clinical application. In this work, we have designed and prepared a streptavidin-based multivalent peptide inhibitor against the HIF-1 alpha-VBC complexation. We have evaluated the potency of the multivalent peptide in terms of stabilization of HIF-1 alpha and the downstream effect. As the result, we have found that the inhibitor showed about 13-fold lowered IC50 value compared with that of the corresponding monovalent peptide, thereby activating HIF-1 alpha and leading to up-regulation of VEGF protein at the cellular level. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: HIF; HYDROXYLASE; INHIBITION; BINDING; FAMILY